The improvement of carbohydrate digestibility in wheat-based diets with Xylanase - Burg, Elizabeth R.; Delfelder, C.J.; Beyer, R. Scott; Stark, Charles R.; Evans, C.E.; Yoder, Ashton D.; Jones, Cassandra K. (My University, 2017)
An increasing problem in agriculture today is the pressure from consumers to reduce the use of antibiotics in poultry feed. However, the producers still must maintain animal welfare. One possibility would be to replace monensin sodium, an ionophorous antibiotic produced by a fungus, with exogenous xylanase. This enzyme is known to improve nutrient digestibility in higher fiber diets, but it’s ability to replace an antibiotic such as monensin sodium is unknown. Therefore, the objective in this research study was to evaluate if xylanase can replace monensin sodium to improve nutrient digestibility, based on the amount of fiber in the diet. A total of 216 Cobb 1-d-old chicks (6 birds/cage) were in battery cages for 21 days, fed ad libitum 1 of 6 dietary treatments. Body weight and feed intake were recorded weekly to determine body weight gain, total feed intake, and FCR. The data collected were analyzed using the GLIMMIX procedure of SAS, with cages being the experimental unit and treatment being the fixed effect. The 6 different types of dietary treatments consisted of a corn- or wheat- based diet, supplemented with either 0.10 g/kg monensin sodium (Coban 90; Elanco Animal Health, Greenfield, IN) or 16,000 betaxylanase units/kg beta 1-4, endoxylanase enzyme (Econase XT; AB Vista, Marlborough, UK). The specific treatments were: 1). corn-based; 2). wheat-based; 3). corn-based with monensin sodium; 4). wheat-based with monensin sodium; 5). corn-based with xylanase; and 6). wheat-based with xylanase. Treatment impacted (P < 0.01) final BW, feed intake, and FCR. The most significant change was FCR. The corn-based control diet improved (P < 0.05) compared to the wheat-based control diet. In the corn-based diet, neither the monensin nor the xylanase improved (P > 0.05) FCR compared to the corn-based control. In the wheat-based diets, xylanase improved (P < 0.05) FCR compared to the wheat-based control, but not monensin sodium (P > 0.05). In conclusion, this experiment shows that xylanase improves digestibility with carbohydrates in wheat-based diets, and restores FCR in corn-based diets. Since the birds were in battery cages, there was little to no use of feeding an antimicrobial in this setting.
Keywords: Spring 2017